IMPLEMENTASI PENDEKATAN TaRL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS X SMKN 1 SURABAYA - Masruroh Khafidhoh; Endah Budi Rahaju; Indah Saptaning Wahyuni (Universitas Muhammadiyah Semarang, 2024)
This study is motivated by the low critical thinking skills of X MP 3 grade students at SMKN 1 Surabaya, where 22 out of 35 students failed to meet the Minimum Competency Criteria (KKM) in the pre-test. Teacher-centered learning often overlooks the varying levels of student understanding, leading to gaps that need to be addressed. This classroom action research aims to improve students' critical thinking skills through the Teaching at the Right Level (TaRL) approach, which is tailored to the specific needs of each student. Conducted in two cycles, the study shows significant improvement in students' critical thinking abilities. The average pre-test score was 51.00 with a 37% pass rate. After implementing TaRL, the average score on the first post-test at the end of the first cycle increased to 70.86 with a 69% pass rate, and the second post-test at the end of the second cycle showed an increase to 83.77 with an 83% pass rate. This improvement indicates progress in interpreting, analyzing, evaluating, and making inferences. TaRL proved to be effective and is recommended for further exploration regarding its long-term impact and scalability in education.